Perbedaan Mental Toughness Ditinjau dari Posisi Bermain, Level Prestasi, dan Jenis Kelamin pada Atlet Voli - Filda Syafira Razanah; Miftahkhul Jannah; Damajanti Kusuma Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine differences in mental toughness among volleyball athletes based on playing position, performance level, and gender. The study employed a quantitative approach with a descriptive comparative design and a cross-sectional method. The sample consisted of volleyball athletes from the Bina Bola Voli (BBV) Club in Surabaya, representing regional, provincial, national, and international levels. Data were collected using the Mental Toughness Index (MTI) and analyzed using a three-way ANOVA. The results indicated that there were no significant differences in mental toughness based on playing position, performance level, or gender, either partially or through their interactions. These findings suggest that mental toughness among volleyball athletes is relatively similar across groups and is more strongly influenced by individual experience and the ability to manage competitive pressure. The results of this study are expected to provide a basis for the development of more individualized and contextual mental training programs for volleyball athletes. Keywords: Volleyball Athletes, Gender, Performance Level, Mental Toughness, Playing Position